On the Difficulty of Comparing the Spatial Distribution of Service Industries Across Nations: Contrasting Spain and Canada - Fernando Rubiera Morollón; Mario Polèse (European Regional Science Association (ERSA), 2011)
The spatial distribution of employment in service industries is compared for Spain and Canada for nine (9) industry classes. The empirical and theoretical literature on modern services stresses the importance of agglomeration economies for high-order services. The relationship between city-size and location is examined with emphasis on cases that deviate from predicted patterns. The results for Spain and Canada reconfirm the weight of city-size as a determinant of location for high-order services. However, once one goes beyond this fairly predictable result, national differences in geography, institutions, and development come to the fore, making generalizations more difficult. Unlike most manufacturing industries, the definition and the spatial behavior of many service sectors is highly sensitive to institutional factors, creating unique patterns largely fashioned by national context.
Keywords: 330